2019
DOI: 10.1177/1741143219864941
|View full text |Cite
|
Sign up to set email alerts
|

Kindergarten teachers’ perceptions of whole-child development: The roles of leadership practices and professional learning communities

Abstract: This study examined the relationships between leadership practices, professional learning communities, teachers’ efficacy beliefs and perceptions of whole-child development in the context of kindergarten education. A sample of 2120 teachers from 153 Hong Kong kindergartens participated in a questionnaire survey. The results showed that principals’ leadership practices had significant effects on all five professional learning community components. Leadership practices were also positively related to teachers’ p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 58 publications
(123 reference statements)
3
28
0
1
Order By: Relevance
“…As the results of this study show, pedagogical leadership is crucial for the quality of pedagogy. Similar findings of the high-quality leadership practices and the teachers' quality pedagogical practices have been made by Keung et al (2019) in their research. They found that leadership practices are directly and positively related to teachers' perceptions of whole-child development.…”
Section: Discussionsupporting
confidence: 81%
“…As the results of this study show, pedagogical leadership is crucial for the quality of pedagogy. Similar findings of the high-quality leadership practices and the teachers' quality pedagogical practices have been made by Keung et al (2019) in their research. They found that leadership practices are directly and positively related to teachers' perceptions of whole-child development.…”
Section: Discussionsupporting
confidence: 81%
“…In Kardos and colleagues study of new teachers in elementary, middle and high schools, the teachers found real professional interaction, and the exchange of ideas and practices, in professional cultures where the school leader had deliberately organized structures to encourage this kind of interaction (Kardos et al, 2001). Similarly, in their study of Hong Kong kindergartens, Keung and colleagues found that leaders' effectiveness at developing PLCs influenced teacher beliefs including shared values and collective efficacy (Keung et al, 2019).…”
Section: Defining Professional Culturementioning
confidence: 99%
“…It led to the introduction of universal (key) competencies into the Federal State Standards of Higher Education in Russia, which reflect key competence "Teamwork and Leadership". Teamwork skills should be formed at all stages of professional activity development, starting (Sidelnikova, 2018). Foreign studies (Keung et al, 2020) emphasize the role of leadership and mediating role of professional learning communities in the professional development of teachers, in development of cooperation.…”
Section: Theoretical Researchmentioning
confidence: 99%
“…Teamwork skills should be formed at all stages of professional activity development, starting (Sidelnikova, 2018). Foreign studies (Keung et al, 2020) emphasize the role of leadership and mediating role of professional learning communities in the professional development of teachers, in development of cooperation. A survey of 153 kindergarten teachers in Hong Kong showed that kindergarten leaders play a key role in fostering education based on organization of interested parties interaction.…”
Section: Theoretical Researchmentioning
confidence: 99%